Proceedings for the Second Symposium on Space Economy, Space Law and Space Sciences - Bayraktar, Yuksel; Alis, Sinan; Akun, Verda Neslihan (Istanbul University Press, 2023)
Space has always been a subject of intense human curiosity. In recent years, space issues have attracted the attention of many scientists, engineers and entrepreneurs around the world. Space exploration holds great potential for the future of mankind, and to realize this potential, we need to focus on space economy, space law and space science. There are many challenges to space exploration, such as high costs, technological challenges, and physical challenges. Overcoming these challenges requires the cooperation of scientists, engineers, space agencies and private companies from around the world. This Symposium Proceedings book contains the written versions of most of the papers presented at the II. International Space Economy, Space Law and Space Sciences Symposium held at Istanbul University on May 28-29, 2022. The symposium was co-organized by Istanbul University Faculty of Economics, Faculty of Law and Observatory Application and Research Center. The aim of the symposium is to learn and support academic studies on space in Turkiye and the world. This symposium has provided an opportunity to discuss the studies and results obtained in the fields of Space Economy, Space Law and Space Sciences, to learn from each other and to carry out joint studies. Thirty-two distinguished researchers from four different countries, 18 different universities, two different companies, APSCO and the Turkish Space Agency came together at the symposium, where twenty-seven qualified papers were presented in five sessions. The President of the Defense Industry and the Minister of Industry and Technology were invited as keynote speakers. The main objective of the symposium was to promote research and activities in space studies and to exchange information on space laws and space economy for the Turkish Space Policy. The presentations of the speakers were related to the needs and conditions of the sector as well as the trends and developments in the economic, legal and scientific aspects of space. The symposium papers present a multidisciplinary approach to space studies and provide insightful information for the Turkish Space Program. In terms of disciplines, astropolitics, cooperation opportunities with APSCO, Space 4.0, the impact of space on international security, opportunities in the space economy, responsibilities arising from space activities, legal dimensions of space activities, commercialization of space, objectives of the Turkish Space Agency, rocket technologies, small satellites and ATASAM R&D infrastructure, and the impact of space activities on economic growth were covered. We thank all the participants for their contributions to the symposium program.